What causes Chinese listed firms to switch bank loan provider? Evidence from a survival analysis - Huang, Jiayi; Matthews, Kent; Zhou, Peng (2020)
This paper analyses the duration of firm-bank relationships and examines what drives firms in China to change from one bank loan provider to another. Matched data of firm-loan-duration to bank provides a unique panel data set of relationship between China's listed firms and their lending banks consisting of 2102 firms listed on both the Shanghai Stock Exchange and Shenzhen Stock Exchange in the period of 1996–2016. The Cox proportional hazard model is used to allow for a semiparametric hazard function after parametrically controlling for firm-specific financial factors, industry factors, ownership characteristics, internal management changes, and external macroeconomic changes. In addition, we explore the impact of the 2008 financial crisis, bank-financial and ownership characteristics. The main finding of this study is that in an environment of growing commercialisation of relationships the firm-bank relationship between state-owned enterprises (SOEs) and state-owned banks (SOBs) in China remains super-stable. However, a change in the CEO of a firm even of a SOE increases the probability of the loan-provider being changed.